Evaluation of a point‐of‐care method for screening blood donors for sickle cell status. (5th March 2020) - Badawi, Maha; Garoot, Sara; Tahlawi, Mofida; Hindawi, Salwa; Adam, Soheir
Abstract : BACKGROUND: Turbidity tests are commonly used for screening blood units for the presence of sickle cell trait (SCT) before transfusion to specific patient populations, based on recommendations of the AABB. In this pilot study, we evaluate a new method for screening blood donors and blood units for the presence of sickle hemoglobin. STUDY DESIGN AND METHODS: This study was based at King Abdulaziz University Hospital in Jeddah, Saudi Arabia. Study participants were approached consecutively between July 24, 2016, and August 8, 2016. Blood donors, control individuals, and known patients with sickle cell disease (SCD) were tested using both a point‐of‐care testing technology (Sickle SCAN, Biomedomics, Inc.) and hemoglobin capillary electrophoresis (HEP). Corresponding blood units were also tested using Sickle SCAN. RESULTS: A total of 200 donors, 13 blood units, and 57 patients and controls were included. Sensitivity and specificity of Sickle SCAN for detection of SCT and SCD was 100%, when compared to HEP as the gold standard. CONCLUSION: Sickle SCAN is a rapid test that shows high sensitivity and specificity for identification of hemoglobin S among blood donors and when used for testing blood units.